Intestinal neuronal dysplasia presenting as psoas abscess: A case report - Ren, Bing Bing; Zhang, Bo; Chen, Shu Xian; Han, Hong Qiu; Sun, Da Qing (Frontiers in Surgery, 2022)
Abstract Background Intestinal neuronal dysplasia (IND) is a rare condition mainly affecting the children. Constipation and abdominal distension have been reported as common manifestations. In addition, the reports about adult cases are scarce. Case report A 31-year-old man presented with pain in his left hip and intermittent fever for 1 month. The whole abdomen CT and pelvic contrast-enhanced MRI revealed a left psoas abscess (PA). The patient has been given anti-infective treatment and underwent CT-guided drainage of left PA with a temporary drain. But the patient's condition did not improve significantly. Then, the colonoscopy revealed that it may be the PA secondary to inflammatory bowel disease. But the pathology was not in line with inflammatory bowel disease. We finally performed an ileostomy surgery and took the whole layer of intestinal wall for biopsy. The pathological result revealed that a large number of proliferative ganglion cells and circuitous hyperplastic nerve fibers were found in the submucosa and muscular layer of the intestinal wall. Given pathological results and clinical manifestations, the patient was diagnosed with IND-B. Conclusion In this case, we first report an extremely rare case of adult IND manifesting as PA. So, this unusual case provides a new supplement to adult cases of IND.